Experience Of Mothers With Chronically Disabled Children In Remote Areas - Setijaningrum, Erna; Mas’udah, Siti (Opción, 2019)
This study aimed to find out how the experience of the mothers with chronical- ly disabled children in remote areas finding ways to overcome their problems. This study employed a qualitative method. The results of this study showed that mothers with chronically disabled children felt stressed, were considered a family disgrace, and experienced discrimination from the community. They tried to find a way to solve their problems by actively participating in the rou- tine activities carried out by their communities. They received a lot of benefits from the activities. They felt more confident, received a lot of information re- garding the care of children with chronic disabilities, were optimistic, empow- ered, patient and accepted the situation.